Media framing of Philip Mehrtens: a critical extension of Entman’s model - Abdurrahman, Muhammad Sufyan; Paulandhika , Michelle Gabriella Virgiallo (Faculty of Communications Science, Dr. Soetomo University, 2026)
The release of Susi Air pilot Philip Mehrtens in September 2024 offers journalism academics an opportunity to reevaluate Robert Entman’s (1993) framing model and their relevance to prolonged conflict reportage. This study examined whether media framing continues to function as an adequate analytical tool for understanding coverage of long-standing conflict zones, which is shaped by political rivalry and deep social division. Using a qualitative framing approach, the authors analysed six online news articles published by national media outlets (Detik.com, Kompas.com, and Republika.co.id) and by local Papuan media (Jubi.id, SuaraPapua.com, and TribunPapua.com). The analysis draws on Entman’s four framing functions: defining problems, diagnosing causes, making moral judgements, and treatment recommendations, to compare how national and local media constructed meaning around the same event. The findings show that while Entman’s framing functions consistently organise news narratives and enable systematic comparison, the model is not analytically adequate when used in isolation. Marked differences in framing orientation reveal the decisive influence of ownership structures, ideological positioning, emotional cues, and historical memory. National media prioritised procedural diplomacy, official chronology, and state authority, whereas local media foregrounded indigenous agency, community leadership, and structural injustice. To address these limitations, this study extends three analytical extensions: institutional constraint, emotional and symbolic framing, and cultural and contextual anchoring. Together, these extensions contribute to strengthening the explanatory capacity of framing analysis in long-standing conflict settings.